2019
DOI: 10.1111/ahg.12336
|View full text |Cite
|
Sign up to set email alerts
|

BBS5 and INPP5E mutations associated with ciliopathy disorders in families from Pakistan

Abstract: Ciliopathies are a clinically and genetically heterogeneous group of disorders often exhibiting phenotypic overlap and caused by abnormalities in the structure or function of cellular cilia. As such, a precise molecular diagnosis is important for guiding clinical management and genetic counseling. In the present study, two Pakistani families comprising individuals with overlapping clinical features suggestive of a ciliopathy syndrome, including intellectual disability, obesity, congenital retinal dystrophy, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…4b, Mann-Whitney test p-value > 0.05). One extreme example is the p.(Arg621Gln) variant, which has been observed as a homozygote in two non-syndromic and one mildly syndromic IRD cases in this study and recently reported in one subject with JBTS with no retinal degeneration 15 disorders, JBTS 10 and MORM 9 , characterized by severe neurological manifestations and extra-neurological symptoms which may differ both quantitatively and qualitatively in each affected individual, even within the same family 10,12,16,21,34 . Therefore, the mostly non-syndromic patients described in this study are on a milder spectrum of the INPP5E disease.…”
Section: Meta-analysis Of All Pathogenic Inpp5e Variants and Their Phenotypic Correlationsupporting
confidence: 62%
“…4b, Mann-Whitney test p-value > 0.05). One extreme example is the p.(Arg621Gln) variant, which has been observed as a homozygote in two non-syndromic and one mildly syndromic IRD cases in this study and recently reported in one subject with JBTS with no retinal degeneration 15 disorders, JBTS 10 and MORM 9 , characterized by severe neurological manifestations and extra-neurological symptoms which may differ both quantitatively and qualitatively in each affected individual, even within the same family 10,12,16,21,34 . Therefore, the mostly non-syndromic patients described in this study are on a milder spectrum of the INPP5E disease.…”
Section: Meta-analysis Of All Pathogenic Inpp5e Variants and Their Phenotypic Correlationsupporting
confidence: 62%
“…Six of these seven genes encode proteins participating in the leptin/melanocortin pathway ( LEP, LEPR (3 variants), PCSK1 (two variants), POMC, ADCY3 , and MC4R ) providing compelling support for the importance of this pathway also in normal growth (Supplementary Table 2). The remaining gene, INPP5E , is implicated in MORM Syndrome (OMIM #610156), a ciliopathy presenting early-onset central obesity 25,26 . Apart from MC4R , the associated variants belong to the Transient and Early Rise clusters, showing that mechanisms at play act very early after birth, some of which in a narrow age window.…”
Section: Resultsmentioning
confidence: 99%
“…Neurological abnormalities may also include Dandy-Walker malformation (DWM), ventriculomegaly, periventricular nodular heterotopia, hydrocephalus, encephalocele/meningocele, polymicrogyria, absence of the pituitary gland, corpus callosum defects and morphological brainstem abnormalities ( 83 , 89 - 91 ). A wide range of clinical signs may be observed, such as hypotonia, ataxia, developmental delay, intellectual disability (ID), impaired or absent speech, behavioral disturbances such as hyperactivity and aggressiveness, and self-mutilation ( 92 , 93 ).…”
Section: Ciliopathiesmentioning
confidence: 99%